Job complexity and learning opportunities: A silver lining in the design of global virtual work - Nurmi, Niina; Hinds, Pamela J (Journal of International Business Studies, 2016)
A vast majority of research on global virtual work focuses on the struggles for workers as they navigate geographic, cultural, language, and time zone differences. Our research suggests that, despite these struggles, global virtual work may offer significant benefits to workers. We interviewed 78 engineers about their experiences of working globally and then surveyed 515 knowledge workers who worked either with globally distributed or exclusively collocated colleagues. Global virtual work was associated with workers’ positive appraisal of the work’s complexity and learning potential, which, in turn, improved innovation, satisfaction, and engagement. These effects, however, relied on workers’ off-job recovery between workdays.